Impact of various cooking methods on the micronutrient compositions of selected legumes in Eastern Nigeria - Emmanuel, Agomuo; Peter, Amadi; Chidiebere, Iheka; Majesty, Duru (International Journal of Biological Research, 2016)
The impact of various methods of cooking on the concentration of some micronutrients in African Breadfruit (Treculia africana), Melon seeds (Citrullus vulgaris), Groundnut (Arachis hypogea), African oil bean (Pentaclethra macrophylla), Cashew nut (Anacardium occidentale) and Coconut (Cocos nucifera) samples were evaluated using standard methods. The results show that only the β-carotene and potassium contents of African Breadfruit were significantly affected by the various forms of heat processing applied. A significant (p<0.05) increase in the β-carotene content was observed for the melon seeds samples on application of heat by boiling (19223.61±4.00mg/100g) and microwave cooking (19028.59±62.12mg/100g), compared to the raw samples (12462.13±39.11mg/100g), which was equally observed for, groundnut, and cashew nut samples. Heat processing by boiling, pressure cooking, and microwave cooking significantly reduced the K content of the melon seeds, while heat processing by frying caused no significant effect. The Mg, Mn, Na, Zn, and Ca contents of the melon seeds were unaffected by the forms of heat applied. For the oil bean samples, the total carotenoid, K, Na, and Ca contents showed a significant decrease on application of the processing methods used in this study, while a similar result was obtained for the heat processed coconut samples, with an additional change in the Mg content, on application of heat. This study has shown that, Boiling, Frying, Pressure cooking and Microwave cooking affected the micronutrient composition of the selected legumes. Cooking by boiling showed the most retention of the micronutrients whereas the frying and microwave cooking methods showed more losses in micronutrient content.